2016
DOI: 10.1088/2053-1583/3/4/045009
|View full text |Cite
|
Sign up to set email alerts
|

Terahertz wave generation and detection in double-graphene layered van der Waals heterostructures

Abstract: We report on the first experimental observation of terahertz emission and detection in a double graphene layered(GL) heterostructure which comprises a thin hexagonal-boron nitride tunnelbarrier layer sandwiched between two separately contacted GLs. Inter-GL population inversion is induced by electrically biasing the structure. Resonant tunneling and negative differential resistance is expected when the two graphene band structures are perfectly aligned. However, in the case of small misalignments we demonstra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
37
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 63 publications
(39 citation statements)
references
References 38 publications
1
37
1
Order By: Relevance
“…The gapless energy spectrum of graphene layers (GLs) [1,2] enables their use in the interband photodetectors [3][4][5][6] (see also the review articles [7][8][9][10][11] and the references therein) and sources (for example, [11][12][13][14][15][16][17][19][20][21][22][23][24][25][26][27][28] operating in the terahertz (THz) a far-infrared (FIR) spectral ranges. In particular, the optical [12,14,[17][18][19][20][21] and lateral injection pumping of the GLs from the side nand p-contacts (i.e., from the chemically-or electricallydoped regions) [13,16,22,[24][25][26][27] can lead to the interband population inversion and negative dynamic conductivity. This can enable the THz lasing experimentally demonstrated.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The gapless energy spectrum of graphene layers (GLs) [1,2] enables their use in the interband photodetectors [3][4][5][6] (see also the review articles [7][8][9][10][11] and the references therein) and sources (for example, [11][12][13][14][15][16][17][19][20][21][22][23][24][25][26][27][28] operating in the terahertz (THz) a far-infrared (FIR) spectral ranges. In particular, the optical [12,14,[17][18][19][20][21] and lateral injection pumping of the GLs from the side nand p-contacts (i.e., from the chemically-or electricallydoped regions) [13,16,22,[24][25][26][27] can lead to the interband population inversion and negative dynamic conductivity. This can enable the THz lasing experimentally demonstrated.…”
Section: Introductionmentioning
confidence: 99%
“…This can enable the THz lasing experimentally demonstrated. The GL-based heterostructure with lateral current injection and the grating providing the distributed feedback exhibits a single-mode lasing at 5.2 THz and a broadband (1 -8 THz) amplified spontaneous emission both at 100 K [24][25][26]. To increase the operating temperature and further enhance the THz gain and lasing radiation intensity, the injection efficiency should be elevated.…”
Section: Introductionmentioning
confidence: 99%
“…To break through these substantial limitations, graphene has attracted attention owing to its gapless and linear energy spectrum and massless Dirac Fermions, giving rise to superior carrier transport properties [27][28][29][30][31]. The latest studies have reported on the potential of relatively simpler multi-layer graphene devices [32,33] to more complex graphene/h-BN heterostructures [34,35] for highly sensitive detection as well as emission of THz radiation [35].…”
Section: Introductionmentioning
confidence: 99%
“…The gapless energy spectrum of graphene layers (GLs) [1] supporting the terahertz (THz) and far-infrared (FIR) radiative interband transitions enables the detection, control, and generation of the THz and FIR radiation (see, for example, the review articles [2][3][4][5][6] and the references therein). One of the most interesting potential application of the GLs and the GL-based heterostructures is their use in efficient THz and FIR lasers that were predicted to operate at room temperature and already demonstrated operation at 100 K [7][8][9][10][11][12][13][14][15][16][17][18][19][20]. Such lasers can be particularly useful in the spectral range below 5 to 10 THz where the operation of the heterostructure lasers based on A 3 B 5 compounds is hampered by a strong radi-ation absorption by the optical phonons.…”
Section: Introductionmentioning
confidence: 99%